Report on the monitoring, evaluation, learning and impact assessment (MELIA) of the circular bioeconomy innovation hub in Ghana - Amoah, P; Drechsel, Pay (International Water Management Institute, 2024)
The Circular BioEconomy Innovation Hub was launched in mid-2023 to create awareness and offer training and research opportunities on proper waste management and recycling for a circular economy and environmental protection. The report provides a first MELIA assessment of the ongoing setup of the Hub in Ghana with special reference to its first major activity, a school awareness program for so far over 12500 students. The report is based on mutually agreed progress indicators. Key learning areas (including challenges and possible solutions to address these) are being flagged and discussed.